Legal Framework for the Protection of Ukrainian Refugees: A Comparative Study - Malanchuk, Illia (Problems of legality, 2023)
The article focuses on the issue of Ukrainian refugees who have been forced to flee abroad due to the ongoing conflict in Ukraine, and the complex and challenging legal framework for their protection. The study reviews relevant literature and previous studies on the legal framework for the protection of refugees, with a particular focus on the situation of Ukrainian refugees. The methodology for this article includes a comprehensive analysis of the existing legal instruments and frameworks that are applicable to refugees, including the 1951 Convention Relating to the Status of Refugees and the Temporary Protection Directive. The study aims to contribute to the ongoing discussion on the legal protection of Ukrainian refugees by providing a detailed analysis of the legal framework and identifying specific areas in need of improvement. The objective of the study is to further examine the legal framework for the protection of Ukrainian refugees and to identify ways in which the current system can be improved to better protect this vulnerable population.